The fate of Robinsonia (Asteraceae): sunk in Senecio, but still monophyletic? - Pelser, Pieter B.; Tepe, Eric J.; Kennedy, Aaron H.; Watson, Linda E. (Phytotaxa, 2013)
Robinsonia is a genus of eight species and is endemic to the Juan Fernández Islands. Previous studies based on ITS phylogenies place Robinsonia deeply nested within Senecio, however its monophyly remains uncertain. In this paper, we use phylogenies reconstructed from plastid, ITS-ETS, and combined data to test its monophyly. Plastid phylogenies support Robinsonia as monophyletic, whereas ITS-ETS trees suggest that Robinsonia berteroi may be more closely related to a South American clade of Senecio species rather than to the remaining Robinsonia species. Maximum parsimony and Bayesian inference analyses of the combined data are congruent with the plastid trees, whereas maximum likelihood analyses are congruent with the ITS-ETS data. Nodal support for either hypothesis is generally low, and Shimodaira-Hasegawa tests in which Robinsonia was either constrained to be monophyletic or to be non-monophyletic showed that these trees do not have significantly lower likelihood scores than trees from unconstrained analyses. Thus the monophyly of Robinsonia remains inconclusive despite additional data and analyses. The results of the present paper further corroborate the results of previous studies that Robinsonia is deeply nested within Senecio. We therefore propose to reduce Robinsonia to synonymy and present new names and combinations of the Robinsonia species under Senecio.